Hepatitis C Virus Genotype Analyses in Chronic Hepatitis C Patients and Individuals With Spontaneous Virus Clearance Using a Newly Developed Serotyping Assay. Issue 1 (13th June 2016) - Yang, Ruifeng; Yang, Xiqin; Xiu, Bingshui; Rao, Huiying; Fei, Ran; Guan, Wenli; Liu, Yan; Wang, Qian; Feng, Xiaoyan; Zhang, Heqiu; Wei, Lai
Abstract : Background: We developed a novel HCV serotyping assay and detected the genotypes in chronic hepatitis C (CHC) patients and individuals with spontaneous viral clearance (SVC). Methods: Nine hundred and ninety‐seven patients were enrolled in a previous study; their samples were genotyped originally using the molecular assays. Among them, 190 patients achieved sustained virological response; the post‐treatment samples were also serotyped. Moreover, 326 samples from follow‐up cohorts were serotyped, among whom 66 were from SVC individuals, and 260 from CHC patients. Results: Nine hundred and fifty‐eight out of 997 samples were available for serotyping, among which 29 samples generated indeterminate serotyping results. The consistency between the genotyping and serotyping assays was 91.50% (850/929). The specificity and sensitivity were 98.45% and 88.77% for genotype 1, 96.42% and 93.97% for genotype 2, and 94.15% and 80.52% for non‐genotype 1 or 2. However, only 41 of 60 genotype‐6 samples were correctly serotyped. Little difference was found in the 190 paired serotyping results. No difference existed in the genotype distribution between the SVC and CHC groups ( P = 0.08). Conclusions: The assay provides an accurate alternative for determining HCV genotypes, whereas it is not recommended for detecting genotype 6. Furthermore, it facilitates identifying the genotypes in SVC individuals. HCV genotype has little impact on SVC.